153 The PHQ-9 as a tool to measure depression in people with multiple sclerosis. Issue 12 (14th November 2019) - Quigley, Suzanne; Beswick, Emily; Macdonald, Pamela; Connick, Peter
Abstract : Background: Depression has a point prevalence of 25% and lifetime prevalence of 50% in people with MS (pwMS). Due to its convenience, the PHQ9 may be a useful tool in clinical practice for screening and monitoring of depression in pwMS Objectives: To evaluate the internal and external reliability of the PHQ-9 measure of depressive symptoms in people with MS. Secondary objectives are; to evaluate the validity of the PHQ-9 as a measure of depressive symptoms in people with MS and to evaluate the acceptability of the PHQ-9 to people with MS Design: A cross section validation study Subjects: People with Multiple Sclerosis Methods: People with MS were recruited from the Rowling Care registry at the Anne Rowling Regenerative Neurology Clinic. Participants complete three questionnaires during a 4 week period using online questionnaires. Statistical analysis will be performed at the end of the study using R Studio Results: The study is ongoing and now in the follow up phase. Provisional results are based on 92 completed participant datasets- Internal reliability of the PHQ-9 using Cronbach's Alpha was 0.88. External reliability of the PHQ-9 using intraclass coefficient was 0.72. Conclusions: Final conclusions are pending due to ongoing data collection.